Evaluasi Pelaksanaan Program Pencegahan Penyakit Demam Berdarah Dengue Ditinjau Dari Aspek Input, Proses Dan Output - Elzina Dina De Fretes; Heny Hendrik (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2020)
The incidence of DHF in Fakfak Regency has increased since the last 3 years so it needs to be evaluated. This research aims to analyze the implementation of the DHF P2P program in terms of input, process and output aspects in the working area of the Fakfak Community Health Center in the City of Fakfak Regency. This type of research is qualitative which is presented exploratively descriptively through in-depth interviews. The subjects of the study were the DHF P2P program coordinator, jumantik cadres, foging officers and the Head of the Puskesmas. Data collected by in-depth interview technique. The results of research on the implementation of the Dengue Hemorrhagic Fever disease prevention program in the Puskesmas Fakfak area were reviewed from the Input aspects: 1) Implementing staff, the knowledge possessed by officers and jumantik cadres was quite good; 2) Allocation of funds comes from BOK and JKN funds, but not sufficient; 3) Other program facilities are available, foging machines are still limited. In terms of Process; 1) Program planning, Â it has been arranged in the KAK (Terms of Reference);2) Implementation has not been maximized, mass foging cannot yet be carried out due to limited funds; 3) Standard and periodical recording and reporting has been carried out in the format provided. Output aspects of DHF morbidity rate in 2017 are still high 42 cases, the rate of larvae free coverage since 2017 has increased and in 2018 until the third trimester reached 80%. In conclusion, the implementation of the DHF P2P program at the Fakfak Health Center has not been effective, obstacles experienced due to limited personnel, limited funds and lack of active community and cross-sectoral involvement. Suggestions for DKK to continue to do promotive and preventive efforts by adding funds, refracting cadres who are not active, adding foging machines and involving the community.Â Keywords : Puskesmas DBD P2P Program, Input, Process and Output